Agro Dealers and Information Communication Technology A Case of Selected Districts of Central Province of Zambia. (Global Journal of Human-Social Science, 2024)
This article explores into the analysis of Balzac s Le Chef d OEuvre inconnu with a particular focus on the portrayal of women and creativity in art It investigates Balzac s handling of the art trade financial aspects and female characters while also delving into Frenhofer s portrayals and the symbolism of la Belle Noiseuse This study underscores the significance of grasping these motifs to gain a deeper understanding of Balzac s work and its societal influence during that period
Keywords: information communication technology; agro dealers; efficiency